A Study of the Relationship Between the Designed Sizes of Tight Fitted Clothing Made from Knitted Fabrics and Their Pressure on the Human Body While Wearing - Nguyen, Quoc Toan; Dinh, Van Hai; Phan, Thanh Thao (Old Journal, 2018)
This article presents the results of the study regarding the relationship between the designed sizes of tight fitted clothing made from knitted fabrics and their pressure on the human body while wearing. The subjects chosen in this study for experiments were 25 healthy school-girls with measurements suited to the size 158B (86-90), five samples of pants made from high elastic warp-knitted fabrics, which are manufactured by Uniqlo Japan. We have developed a method of evaluating comfort pressure on school-girls thigh areas by defining the relationship between the pressure and the subjective feeling of wearers. The correlation between pressure and elasticity of the fabrics was investigated using linear regression equations, based on this correlation to calculate the sizes of pant legs according to the comfort pressure values on thigh areas of wearers.